Topological Characterizations for Sheaf of the Groups Formed by Topological Generalized Groups - Hakan Efe; Hatice Aslan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In the present paper, we providethe some algebraic topologicalcharacterizations for an algebraic sheafby means of the topological generalized group constructed in [3] by consideringboth homotopy and sheaf theory.